2002
DOI: 10.1111/1467-646x.00081
|View full text |Cite
|
Sign up to set email alerts
|

Voluntary Disclosure by State‐owned Enterprises Listed on the Stock Exchange of Hong Kong

Abstract: This study examines the impact of international capital market pressures on the voluntary disclosure of three types of information (strategic, financial, and non-financial) in the annual reports of former wholly state-owned People's Republic of China (PRC) enterprises, listed on the Stock Exchange of Hong Kong (SEHK). Consistent with a cost-benefit framework, we find that PRC H-Share firms disclose significantly more strategic and financial information than other SEHK firms. Additional analysis of disclosures … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

18
127
1
3

Year Published

2006
2006
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 178 publications
(149 citation statements)
references
References 22 publications
18
127
1
3
Order By: Relevance
“…Also, as reported by Haniffa and Cooke (2002), foreign owners appear to need more disclosure, owing to the fact that the foreign owners' management needs monitoring. Then, as far as companies are concerned, those that release more disclosure appear to be registered on a number of stock exchanges (Ferguson et al, 2002).…”
Section: Ownership Structure Foreign Ownershipmentioning
confidence: 99%
“…Also, as reported by Haniffa and Cooke (2002), foreign owners appear to need more disclosure, owing to the fact that the foreign owners' management needs monitoring. Then, as far as companies are concerned, those that release more disclosure appear to be registered on a number of stock exchanges (Ferguson et al, 2002).…”
Section: Ownership Structure Foreign Ownershipmentioning
confidence: 99%
“…Ferguson, Lam and Lee (2002), suggested that companies in identifiable, highly competitive industries might disclose less information to prevent loss from the leakage of proprietary information. Malone et al (1993) and Wallace, Naser, and Mora (1994) also argued that the adoption of industry related practices may lead to varied levels of disclosure on similar items in financial reports of companies in different industries.…”
Section: Internationalitymentioning
confidence: 99%
“…Voluntary disclosure in annual reports has been the subject of a great deal of empirical research (e.g., Chau & Gray, 2002;Chow & Wong-Boren, 1987;Cooke, 1989Cooke, , 1991Eng & Mak, 2003;Ferguson, Lam, & Lee, 2002;Firth, 1979;Haniffa & Cooke, 2002;Ho & Wong, 2001a;Hossain, Tan, & Adams, 1994;Hossain, Perera, & Rahman, 1995;Inchausti, 1997;McNally, Eng, & Hasseldine, 1982;Raffournier, 1995;Wallace, Naser, & Mora, 1994;Wallace & Naser, 1995).…”
Section: Prior Literaturementioning
confidence: 99%